2018
DOI: 10.1038/s41557-018-0171-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the strong Brønsted acid site in a metal–organic framework solid acid catalyst

Abstract: It remains difficult to understand the surface of solid acid catalysts at the molecular level, despite their importance for industrial catalytic applications. A sulfated zirconium-based metal-organic framework, MOF-808-SO4, has previously been shown to be a strong solid Brønsted acid material. In this report, we probe the origin of its acidity through an array of spectroscopic, crystallographic, and computational characterization techniques. The strongest Brønsted acid site is shown to consist of a specific ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
218
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(234 citation statements)
references
References 41 publications
(17 reference statements)
7
218
3
Order By: Relevance
“…[13][14][15][16][17][18] MOFs, with site isolation and adjacent active catalytic sites, which have been obtained throughd irect use or postsynthetic functionalization, as single-site and cooperative catalysts for chemical transformations have been investigated. [19][20][21][22][23][24][25][26][27] Ta king advantage of their frequently occurring reversible structural transformations, through single-crystal to single-crystal processes,t he uniquef lipping motion between structurala nd topologyc onnectionsa re similart oe ach otherm akes MOFs a highly appropriate choice for building molecular devices,s uch as switching or sensing materials. [28][29][30][31][32] Meanwhile,s olvent-induced dissolution-exchange-crystallization behavior is another important,but difficult, approach to regulating reversible structural transformations because the connection modesb etween metal ions and ligandsa re very difficult to re-edit.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] MOFs, with site isolation and adjacent active catalytic sites, which have been obtained throughd irect use or postsynthetic functionalization, as single-site and cooperative catalysts for chemical transformations have been investigated. [19][20][21][22][23][24][25][26][27] Ta king advantage of their frequently occurring reversible structural transformations, through single-crystal to single-crystal processes,t he uniquef lipping motion between structurala nd topologyc onnectionsa re similart oe ach otherm akes MOFs a highly appropriate choice for building molecular devices,s uch as switching or sensing materials. [28][29][30][31][32] Meanwhile,s olvent-induced dissolution-exchange-crystallization behavior is another important,but difficult, approach to regulating reversible structural transformations because the connection modesb etween metal ions and ligandsa re very difficult to re-edit.…”
Section: Introductionmentioning
confidence: 99%
“…The acidity of the synthesized 2D solid acids was investigated by using 1 H and 31 P MAS NMR, a reliable and state-of-the-art technique for determination of the acidity of solid acid catalysts. 6,9,24,38,39 In particular, 31 P trialkylphosphine (TMP) NMR has been used to distinguish Brønsted and/or Lewis acid types. When TMP molecules are bound to Lewis acid sites, they give rise to 31 P resonance ranging from ca.…”
Section: Resultsmentioning
confidence: 99%
“…The schematic representation was shown in Figure . The Brønsted acid site not only came from P‐OH group, but also arose from the hydrogen‐bonding interaction between water and sulfate ,, , . Trickett et al.…”
Section: Resultsmentioning
confidence: 99%
“…concluded that the Brønsted acid site was correlated with the number of binding water in the catalyst. The Brønsted acid site in the sulfated catalyst originated from a weakly bound proton between two bases (a sulfate and a hydroxyl from water molecule) . In this work, the O−H bond from water molecule formed hydrogen bond with adjacent sulfate, resulting in the increase of Brønsted acid sites.…”
Section: Resultsmentioning
confidence: 99%